Kekuatan Online Customer Review: Meningkatkan Perceived Value dan Memicu Impulse Buying (Studi Kasus Konsumen Skintific di Shopee Kabupaten Morowali) - Risma, Risma; Auriza, Moh. Zeylo; Bachri, Syamsul; Wanti, Sri (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2026)
The purpose of this study was to identify the influence of online customer reviews (OCR) on perceived value and impulse buying behavior for Skintific products. The study was conducted in the Bungku Tengah region, focusing on the Shopee platform. The study used a quantitative approach and purposive sampling technique as the respondent selection method. Data were collected through an online questionnaire distributed to 110 respondents who had purchased Skintific products on Shopee. Data processing was carried out using the Structural Equation Modeling (SEM) method using AMOS software version 22. The analysis results showed that OCR had a positive and significant influence on perceived value. Furthermore, OCR was also proven to significantly influence impulse buying behavior, meaning that consumer reviews can lead other consumers to make unplanned purchases. Another finding was that when consumers evaluate a product positively, the tendency to make spontaneous purchases increases.